The design and analysis of seroefficacy studies for typhoid conjugate vaccines - Liu, X; Pitzer, V; Pollard, A; Voysey, M (Oxford University Press, 2019)
Background Demonstrating efficacy of new Vi-conjugate typhoid vaccines is challenging due to the cost of field trials requiring tens of thousands of participants. New trial designs that use serologically-defined typhoid infections (seroefficacy trials) rather than blood culture positivity as a study endpoint may be useful to assess efficacy using small trials. Methods We developed a model for Vi-IgG antibody response to a Vi-vaccine, decay over time, and natural boosting due to endemic exposures. From this we simulated clinical trials in which two blood samples were taken during follow-up, and the relative risk of serologically-defined typhoid infection (seroefficacy) was computed. We aimed to determine if seroefficacy trial designs could substantially reduce sample sizes compared with trials using blood-culture-confirmed cases; if case detection was higher in seroefficacy trials; and the optimal timing of sample collection. Results The majority (>90%) of blood-culture-positive typhoid cases remain unobserved in surveillance studies. In contrast, underdetection in simulated seroefficacy trials of equivalent vaccines was as little as 26%, and estimates of the relative risk of typhoid infection were unbiased. For simulated trials of non-equivalent vaccines, relative risks were slightly inflated by at least 5% depending on sample collection times. Seroefficacy trials required as few as 460 participants per arm, compared with 10,000 per arm for trials using blood-culture-confirmed cases. Conclusion Seroefficacy trials can establish the efficacy of new conjugate vaccines using small trials enrolling hundreds rather than thousands of participants, and without the need for resource-intensive typhoid fever surveillance programmes.